2005
DOI: 10.1364/ol.30.001129
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of spectral features readout with frequency-chirped laser fields

Abstract: A data-processing technique is proposed for use with conventional frequency-chirped absorption spectroscopy to ensure accurate mapping of spectral features into time-domain signatures with arbitrarily fast readout chirp rates. This technique recovers the spectrum from a signal that is distorted owing to the fast chirp rate and therefore facilitates fast measurement of the spectral features over a broad spectral range with high resolution. Both numerical simulations and experimental results are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 8 publications
(2 reference statements)
1
24
0
Order By: Relevance
“…For most comb measurements we chose to scan the laser over one peak only and lowered the scan rate to a minimum. This is to reduce the effect of the scan rate on the measurement resolution [40,35]. By varying the rate we confirmed that the measured width was indeed independent of the scan rate.…”
Section: Comb Structure Measurementsupporting
confidence: 56%
“…For most comb measurements we chose to scan the laser over one peak only and lowered the scan rate to a minimum. This is to reduce the effect of the scan rate on the measurement resolution [40,35]. By varying the rate we confirmed that the measured width was indeed independent of the scan rate.…”
Section: Comb Structure Measurementsupporting
confidence: 56%
“…Because of the better chirp spectral purity, the readout gets the behavior predicted in Ref. [8]. Indeed, one can see the expected ringing in the detected signal.…”
Section: Article In Pressmentioning
confidence: 59%
“…In all this discussion, we neglect the linear dispersion associated with interrogating narrow holes with fast chirps [8]. Since E RF and E P are collinear, the detected intensity is given by…”
Section: Article In Pressmentioning
confidence: 99%
See 2 more Smart Citations